Association of Early Supplemental Parenteral Nutrition with Clinical Outcomes in Patients with Traumatic Brain Injury - Heejin Kim; Jingyeong Kim; Jihyeon Ahn; Mihwa Jang; Eunyoung Kim; Dae-Sang Lee; Min Ho Lee; Hyung Sun Choi; Maru Kim (Journal of Korean Neurosurgical Society, 2026)
Objective : Early oral or enteral nutrition (EN) is recommended for critically ill patients; however, individuals with traumatic brain injury (TBI) often fail to meet their nutritional goals. Supplementary parenteral nutrition (SPN) in this instance may be of benefit, but evidence is lacking. This study examined the association between early SPN and nutritional adequacy and clinical outcomes in patients with TBI.Methods : This retrospective, non-randomized, single-center cohort study analyzed adult patients with TBI admitted to a trauma intensive care unit (ICU) from January 2023 to December 2024. Patients who received oral nutrition or EN on hospital day 4 (HD4) were included and classified based on their use of SPN. We assessed total caloric and protein intake on HD4, as well as survival rates, lengths of ICU and hospital stays, the occurrence of infectious complications, and unplanned ICU readmissions.Results : Among 260 screened patients, 122 were included in the study. The SPN group achieved higher caloric intake (1508 vs. 852 kcal; p